Geographical Latitude Remains as an Important Factor for the Prevalence of Some Myositis Autoantibodies: A Systematic Review - Aguilar-Vazquez, Andrea; Chavarria-Avila, Efrain; Pizano-Martinez, Oscar; Ramos-Hernandez, Alejandra; Andrade-Ortega, Lilia; Rubio-Arellano, Edy-David; Vazquez-Del Mercado, Monica (Frontiers in Immunology, 2021)
The idiopathic inflammatory myopathies (IIM) are characterized by muscular weakness, cutaneous manifestations, muscle damage revealed by increase of muscular enzymes, muscle biopsy, electromyography and changes on magnetic resonance imaging. However, the hallmark of these IIM, is the development of myositis specific antibodies (MSA) or myositis associated antibodies (MAA). The theories about their presence in the serum of IIM is not known. Some studies have suggested that some of these MSA, such as anti-Mi-2 increases according to the intensity of UV radiation. There is scarce information about the environmental factors that might contribute in order to be considered as triggering factors as UV radiation might be. In this review, we analyzed the reported prevalence of MSAs and MAAs regarding to their geographical location and the possible relation with UV radiation. We collected the prevalence data of fifteen MSA and thirteen MAA from 22 countries around the world and we were able to observe a difference in prevalence between countries and continents. We found differences in anti-PL7, anti-Ro52, anti-La and anti-Ku prevalence according to UV radiation level. Otherwise, we observed that anti-Mi-2 prevalence increases near to the Equator meanwhile anti-MJ/NXP2 and anti-ARS prevalence had an opposite behavior increasing their prevalence in the geographical locations farther to the Equator. Our results highlighted the importance to include the UV radiation and other environmental factors in IIM studies, in order to to clarify its association with MSA and MAA prevalence as well as its possible role in the immunopathogenesis of these diseases.